2005
DOI: 10.1248/cpb.53.471
|View full text |Cite
|
Sign up to set email alerts
|

Formation Constants of Chromium(III), Scandium(III) and Yttrium(III) Complexes of Some Hydroxy Naphthoic Acids

Abstract: We continue our studies on the complex equilibria between Cr(III), Sc(III), Y(III) and 1-hydroxy-2-naphthoic acid (1,2-HNA: H 2 L) and 3-hydroxy-2-naphthoic acid (3,2-HNA: H 2 L). We have reported the stabilities of the complexes between these metal ions and the title ligands. [1][2][3][4][5][6][7][8][9][10][11] The structural formulas of the studied ligands are shown in Fig. 1. There have been some reports on the Sc(III) and Y(III) complexes of hydroxy naphthoic acids [12][13][14][15] ; but almost nothing is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In previous studies, we demonstrated the coordination of Cr(III) to salicylic acid and its derivatives and to hydroxynaphthoic acids, and we also described the stabilities of various complex species of Cr(III). …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In previous studies, we demonstrated the coordination of Cr(III) to salicylic acid and its derivatives and to hydroxynaphthoic acids, and we also described the stabilities of various complex species of Cr(III). …”
Section: Introductionmentioning
confidence: 90%
“…In previous studies, we demonstrated the coordination of Cr(III) to salicylic acid and its derivatives and to hydroxynaphthoic acids, and we also described the stabilities of various complex species of Cr(III). [22][23][24][25][26] The stoichiometric protonation constants of these two ligands and the stoichiometric stability constants of Cr(III)-hydroxamic acid complexes were calculated.…”
Section: Introductionmentioning
confidence: 99%
“…We performed our research project 12,[19][20][21] from 1996-1998 to define the total Cr, Cr(III) and Cr(VI) concentrations in the river. The total chromium concentrations measured were 0.970-0.090 mg/l range.…”
Section: Complexation Of Cr(iii) In Discharge Watermentioning
confidence: 99%
“…At present, there are no particular materials proposed for effective removal of yttrium ions from water disposals especially when their concentrations are very low. Up to date, there are just a few of published studies devoted to investigation of the properties of materials interacting with yttrium ions such as hydroxy-naphthoic acids (Aksoy et al 2005) and dihydroxybenzoic acids (Aydin and Ozer 2004). Application of these substances for removal of yttrium ions from water disposals is almost impossible due to their low molecular weight and complicated processes of separation from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%